Do Electoral Rules Make Legislators Differently Responsive to Fiscal Transfers? Evidence from German Municipalities - Marko Köthenbürger; Peter Egger; Michael Smart (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The paper empirically analyzes whether electoral rules make legislators differently responsive to changes in fiscal incentives. Key to the analysis are two unique reforms in the German state of Lower Saxony which changed (i) the municipal charter by replacing the council-manager system (featuring appointed mayors) by a mayor-council system (with directly-elected mayors) and (ii) the fiscal incentives inherent to the equalization system. We find that municipalities with appointed mayors react less strongly to changes in fiscal incentives. The change in municipal tax rates is three times smaller compared with a system of direct mayoral elections. We point to the different electoral incentives of mayors in the two systems to explain the result.
Keywords: D78; H70; D72; 330